Antimalarial Activities of Moringa Oleifera Leaf Extract Against Plasmodium Berghei ANKA Infection in ICR Mice - Dondee, Kittiyaporn; Bootprom, Panatda; Saiphet, Butsarat; Borkaew, Preeyanuch; Klubsri, Chokdee; Somsak, Voravuth (International Journal of Innovative Research in Medical Science, 2016)
Malaria caused by Plasmodium malaria parasite is a major public health problem in tropical and subtropical areas. However, the recent reports on malaria parasite resistant to antimalarial drugs highlight the need for new approaches to antimalarial chemotherapy. Hence, the study was aimed to investigate the antimalarial activity of M oleifera leaf extract against P. berghei infection in mice. Aqueous crude extract of M. oleifera leaves was freshly prepared, and acute toxicity test was then carried out in mice. For efficacy test in vivo, suppressive and curative tests were used to evaluate antimalarial activity in P. berghei ANKA infected mice administered orally of the extract (100, 1,000, and 2,000 mg/kg). Percent parasitemia and mean survival time were subsequently monitored. The results showed that the aqueous crude extract of M oleifera leaves at doses of 100, 1,000, and 2,000 mg/kg exhibited suppressive and curative activities with significant (p<0.05) at dose-dependent manners. Moreover, 1,000 and 2,000 mg/kg of the extract treated mice lived longer than the corresponding untreated control with significant (p<0.05). It could be concluded that the aqueous crude extract of M. oleifera leaves demonstrated suppressive and curative antimalarial activities against P. berghei ANKA infection in mice.